Jedi mind tricks: Lennie Tristano and techniques for imaginative musical practice - Jago, Marian S. (Jazz Research Journal, 2015)
In the 1940s, pianist Lennie Tristano was among the first to attempt to teach jazz improvisation as an area of study distinct from instrumental technique. In doing so, he employed a methodology which was considered highly unorthodox at the time and which is still somewhat unique for jazz pedagogy. Chief among these unorthodox pedagogical devices was the use of visualization and other mental techniques for musical practice and composition. These methods enabled students to separate imaginative musical experiences from the habits of muscle memory, while at the same time speeding the acquisition of certain digital techniques and developing the musical imagination. Visualization techniques also served to extend available practice time for students who lacked space suited to audible instrumental practice, and to those who were working day jobs and had limited time available for instrumental practice. Recent studies in brain plasticity bear out Tristano’s intuitive use of mental techniques as a useful addendum to more traditional forms of instrumental and compositional practice. Though certainly not the first to emphasize the importance of mental conditioning and imaginative practice methods, Tristano’s use of them within a methodology for jazz instruction constitutes a unique pedagogical approach worthy of further research and discussion.